Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Harnessing arabica and canephora coffee cascara as substrates for kombucha: Comparative study of chemical, antioxidant, antibacterial and antifungal properties - Mariana Moysés Delorme; Beatriz Spena Machado; Fernanda dos Santos Ferreira; Rayssa Neves Alves; Daniel Coelho Ferreira; Jessica Pronestino de Lima Moreira; Vanessa Naciuk Castelo-Branco; Thais Matsue Uekane; Fabrício Freitas Fernandes; Adriene Ribeiro Lima (Biocatalysis and Agricultural Biotechnology, 2025)

The influence of birth date via body mass on individual fitness in a long‐lived mammal - Floriane Plard; Jean-Michel Gaillard; Tim Coulson; A. J. Mark Hewison; Mathieu Douhard; François Klein; Daniel Delorme; Claude Warnant; Christophe Bonenfant (Ecology, 2015)
The timing of birth has marked impacts on early life and early development of newborns in many species. In seasonal environments, early‐born offspring often survive and grow better than late‐born offspring, but despite the long‐lasting effects of early conditions on life history traits, the influence of birth date on fitness has rarely been investigated for long‐lived species. In this study, we analyzed both the short‐ and long‐term effects of birth date on individual life history traits and explored its subsequent impact on individual fitness in a population of roe deer. We considered both the direct effects, as well as the indirect effects of birth date mediated through the effects of body mass, on demographic parameters. We found that in addition to short‐term effects on early body growth and survival, birth date generates “silver spoon” effects on adult life history traits of female roe deer. Birth date had long‐lasting effects on female adult body mass such that early‐born females were, on average, 3 kg heavier as adults than late‐born females, although female adult survival was similar between these categories. Based on the observed relationships between birth date, body mass, and demographic parameters, we built an integral projection model describing the simultaneous distributions of birth date and body mass to quantify the fitness consequences of birth date. We found that the fitness of early‐born females was higher than that of late‐born females. These long‐lasting effects of birth date on fitness were mostly mediated through the influence of birth date on recruitment and adult body mass. By determining development of newborns during the early stages of life, birth date has a critical influence on each step of an individual's subsequent life history trajectory.

Variation in adult body mass of roe deer: early environmental conditions influence early and late body growth of females - Mathieu Douhard; Jean-Michel Gaillard; Daniel Delorme; Gilles Capron; Patrick Duncan; François Klein; Christophe Bonenfant (Ecology, 2013)
There is increasing evidence that environmental conditions experienced early in life can markedly affect an organism's life history, but the pathways by which early environment influences adult phenotype are poorly known. We used long‐term data from two roe deer ( Capreolus capreolus ) populations (Chizé and Trois‐Fontaines, France) to investigate the direct and indirect (operating through fawn body mass) effects of environmental conditions during early life on adult body mass. We found that environmental conditions (population size and spring temperatures) around birth influenced body mass of adult females through both direct and indirect effects in both populations. The occurrence of direct effects means that, for a given fawn body mass, adult female mass decreases with adverse conditions in early life. In contrast, we found no evidence for direct effects of early‐life conditions on adult body mass of males, suggesting the existence of sex‐specific long‐term responses of body mass to stressful early conditions. Our results provide evidence that early environmental conditions influence the adult phenotype through persistent effects over the body development in wild mammal populations.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Population density and phenotypic attributes influence the level of nematode parasitism in roe deer - Guillaume Body; Hubert Ferté; Jean-Michel Gaillard; Daniel Delorme; François Klein; Emmanuelle Gilot-Fromont (Oecologia, 2011)

Maternal and individual effects in selection of bed sites and their consequences for fawn survival at different spatial scales - Bram Van Moorter; Jean-Michel Gaillard; Philip D. McLoughlin; Daniel Delorme; François Klein; Mark S. Boyce (Oecologia, 2009)

Big mothers invest more in daughters – reversed sex allocation in a weakly polygynous mammal - A. J. Mark Hewison; Jean‐Michel Gaillard; Petter Kjellander; Carole Toïgo; Olof Liberg; Daniel Delorme (Ecology Letters, 2005)
How mothers allocate resources to offspring is central to understanding life history strategies. High quality mothers are predicted to favour investment in sons over daughters when to do so increases inclusive fitness. This is the case in ungulates with polygynous mating systems, where reproductive success is more variable among males than females, but information is scarce on sex allocation in less polygynous species. Here, for the weakly dimorphic roe deer, we show that as maternal capacity to invest increases, mothers increase allocation to daughters more than to sons, so that relative allocation to daughters increases markedly with increasing maternal quality. This cannot be explained by a between sex difference in growth priority, hence we conclude that this is evidence for active maternal discrimination. Further, we demonstrate that condition differences between offspring persist to adulthood. For high quality mothers of weakly polygynous species, daughters may be more valuable than sons.

Contradictory findings in studies of sex ratio variation in roe deer ( Capreolus capreolus ) - A. J. Mark Hewison; Reidar Andersen; Jean-Michel Gaillard; John D. C. Linnell; Daniel Delorme (Behavioral Ecology and Sociobiology, 1999)

Early survival in roe deer: causes and consequences of cohort variation in two contrasted populations - Jean-Michel Gaillard; Jean-Marie Boutin; Daniel Delorme; Guy Van Laere; Patrick Duncan; Jean-Dominique Lebreton (Oecologia, 1997)